Revolutionizing cancer treatment: enhancing CAR-T cell therapy with CRISPR/Cas9 gene editing technology - Tao, Ruiyu; Han, Xiaopeng; Bai, Xue; Yu, Jianping; Ma, Youwei; Chen, Weikai; Zhang, Dawei; Li, Zhengkai (Frontiers in Immunology, 2024)
CAR-T cell therapy, a novel immunotherapy, has made significant breakthroughs in clinical practice, particularly in treating B-cell-associated leukemia and lymphoma. However, it still faces challenges such as poor persistence, limited proliferation capacity, high manufacturing costs, and suboptimal efficacy. CRISPR/Cas system, an efficient and simple method for precise gene editing, offers new possibilities for optimizing CAR-T cells. It can increase the function of CAR-T cells and reduce manufacturing costs. The combination of CRISPR/Cas9 technology and CAR-T cell therapy may promote the development of this therapy and provide more effective and personalized treatment for cancer patients. Meanwhile, the safety issues surrounding the application of this technology in CAR-T cells require further research and evaluation. Future research should focus on improving the accuracy and safety of CRISPR/Cas9 technology to facilitate the better development and application of CAR-T cell therapy. This review focuses on the application of CRISPR/Cas9 technology in CAR-T cell therapy, including eliminating the inhibitory effect of immune checkpoints, enhancing the ability of CAR-T cells to resist exhaustion, assisting in the construction of universal CAR-T cells, reducing the manufacturing costs of CAR-T cells, and the security problems faced. The objective is to show the revolutionary role of CRISPR/Cas9 technology in CAR-T cell therapy for researchers.